American uniqueness revisited: A comparative examination of two school shootings using the path to intended violence - Schildkraut, Jaclyn (International journal of comparative and applied criminal justice, 2024)
Although often perceived to be a uniquely American phenomenon, mass shootings in schools across the globe have led to continued concerns about how to keep educational institutions safe. To identify opportunities for intervention and prevention of these tragedies, this study utilises a comparative case study approach. Specifically, we analyse the events leading up to the mass shootings at Municipal School Tasso da Silveira in Rio de Janeiro (Realengo district), Brazil (2011) and Marjory Stoneman Douglas High School in Parkland, Florida (2018). Using the Path to Intended Violence model, we find that the perpetrators’ pre-attack behaviours, escalating from grievances to the attacks themselves, are remarkably similar despite cultural differences and that multiple opportunities for intervention existed. Implications from these findings related to prevention, school security, and broader policy are considered.